The Implementation of Problem Based Learning (PBL) in Encouraging Independent Learning in Grade 8 at SMP PAB 8 Sampali - Nurhartini; Neni Afrida Sari Harahap; Karunia Devi Frida (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2025)
This study aims to explore how the implementation of Problem-Based Learning (PBL) supports independent learning among Grade 8 students at SMP PAB 8 Sampali. A descriptive qualitative approach was employed, with data collected through questionnaires distributed to 11 students using a Likert scale. The findings reveal that most PBL components were effectively implemented, including the use of real-world problems, the teacher's role as a facilitator, interdisciplinary learning, critical thinking, reflection, and the development of lifelong learning skills. However, elements that require greater student participation such as active problem-solving and choosing how to learn were found to be less developed. PBL was shown to enhance students' time management, responsibility, self-assessment, and curiosity. Despite this progress, some students still heavily relied on teacher guidance, indicating a gap in their ability to learn on their own. Therefore, it is recommended that teachers provide additional support to build students’ confidence and thinking skills, helping them become more independent in their learning. Overall, PBL is proven to be an effective strategy for promoting independent learning, although its success depends on how ready students are to take charge of their own learning.